2011
DOI: 10.1128/aem.01952-10
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Functional Analyses of Rhodococcus equi Phages ReqiPepy6, ReqiPoco6, ReqiPine5, and ReqiDocB7

Abstract: The isolation and results of genomic and functional analyses of Rhodococcus equi phages ReqiPepy6, ReqiDocB7, ReqiPine5, and ReqiPoco6 (hereafter referred to as Pepy6, DocB7, Pine5, and Poco6, respectively) are reported. Two phages, Pepy6 and Poco6, more than 75% identical, exhibited genome organization and protein sequence likeness to Lactococcus lactis phage 1706 and clostridial prophage elements. An unusually high fraction, 27%, of Pepy6 and Poco6 proteins were predicted to possess at least one transmembran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 81 publications
5
76
1
Order By: Relevance
“…Genome similarities between phages infecting different bacterial genera have been seen previously, including the Mu-like phages, P2-like phages, and the lambdoid phages. Furthermore, we note that the Rhodococcus equi phage ReqiPine5 and mycobacteriophage Rosebush (cluster B bacteriophage) share multiple homologous gene pairs located syntenously along their genomes, indicating that these phages are likely to be related (33).…”
Section: Resultsmentioning
confidence: 99%
“…Genome similarities between phages infecting different bacterial genera have been seen previously, including the Mu-like phages, P2-like phages, and the lambdoid phages. Furthermore, we note that the Rhodococcus equi phage ReqiPine5 and mycobacteriophage Rosebush (cluster B bacteriophage) share multiple homologous gene pairs located syntenously along their genomes, indicating that these phages are likely to be related (33).…”
Section: Resultsmentioning
confidence: 99%
“…Despite not identifying smaller contigs that assembled into contig89 on Day 60 (Figure 3, Panel a), we were able to verify that the full contig was present at this time point (Figure 4). We found many putative open reading frames in contig89 that had synteny with Rhodococcus phage Pepy6 and Poco6 (Summer et al, 2011), which are siphoviruses similar to others found in Lactococcus and Clostridium. These data verify that viral genotypes in the human oral cavity are highly persistent, and that some may persist for at least 60 days.…”
Section: Identification Of Virusesmentioning
confidence: 94%
“…We did not perform detailed comparisons of viral genotypes and the bacteria present in each subject because our BLAST-based techniques for characterizing viruses generally are considered insufficient to accurately predict the hosts of each virus. (Summer et al, 2011) are labeled gp054, gp065, gp067, gp068, gp069, gp071, gp072, gp105 and gp106. The location of polymorphisms (when compared with a majority rule consensus from all time points combined) are indicated by orange vertical lines.…”
Section: Discussionmentioning
confidence: 99%
“…This genome is organized as a circularly permuted double-stranded DNA molecule of 74,431 bp with a GϩC content of 56.8 mol%. At the DNA level, only 6% of the sequence shares similarity with that of the phage ReqiDocB7 genome (20), and the remainder (94%) shares no sequence similarity to any other DNA sequence in GenBank. The GTE7 phage genome has 102 putative open reading frames (ORFs) and one tRNA.…”
mentioning
confidence: 99%